2013
DOI: 10.1016/j.jimonfin.2012.05.029
|View full text |Cite
|
Sign up to set email alerts
|

What determines Euro area bank CDS spreads?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
137
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 197 publications
(148 citation statements)
references
References 61 publications
10
137
1
Order By: Relevance
“…Gilchrist et al (2011) for instance demonstrated the importance of considering the business cycle perspective in explaining the determinants of credit spreads. Similarly, Berndt et al (2005) suggest that CDS spreads are likely not attributed to credit risk alone and Annaert et al (2013) notably conclude that liquidity and global economic variables are important to explain CDS variations. More recently, Keiler and Eder (2013) investigate the degree of systemic risk and the importance of potential spill-over effects in the banking system by analyzing the determinants of CDS spreads using spatial econometric approach.…”
Section: The Determinants Of Credit and Cds Spreadsmentioning
confidence: 99%
See 4 more Smart Citations
“…Gilchrist et al (2011) for instance demonstrated the importance of considering the business cycle perspective in explaining the determinants of credit spreads. Similarly, Berndt et al (2005) suggest that CDS spreads are likely not attributed to credit risk alone and Annaert et al (2013) notably conclude that liquidity and global economic variables are important to explain CDS variations. More recently, Keiler and Eder (2013) investigate the degree of systemic risk and the importance of potential spill-over effects in the banking system by analyzing the determinants of CDS spreads using spatial econometric approach.…”
Section: The Determinants Of Credit and Cds Spreadsmentioning
confidence: 99%
“…One of the few research performed specifically on banks and covering the period after the subprime crisis is provided by Annaert et al (2013). Analyzing the determinants of CDS spread changes for 32 listed euro area banks over the period 2004 -2010, they find an increasing explanatory power of the variables suggested by structural credit models after the crisis period.…”
Section: The Determinants Of Credit and Cds Spreadsmentioning
confidence: 99%
See 3 more Smart Citations